STEREOTYPING OF INFERIOR-SUPERIORITY IN “CAESAR AND CLEOPATRA” (1945) DRAMA BY GEORGE B SHAW - Zulfiana Dessyka Putri (IdeBahasa, 2021)
This article aimed to reveal various forms of arbitrary stereotypes between who is perceived as superior and who is perceived as inferior. By taking data from the play Caesar and Cleopartra (1945) by George B Shaw, the researcher examined various discriminatory and tendentious stereotyping phenomena. Although this drama was raised and raised by the western world by involving the east in it, this is what then triggers a new problem of discriminatory inequality between the west and the east which then forms discriminatory perceptions. By using the postcolonial approach, especially Edward Said's orientalism, the researcher uncovers various myths and phenomena. The method used in this research is a qualitative method with a library data collection system and deep critical analysis. The results of this study indicate that the form of incidental and oriental stereotyping is clearly seen through the depiction in the story. The West through the character of Caesar who represents white superiority carries out various orientalist practices on the character of Cleopatra as a representation of the east. All are quoted in their actions, attitudes, character, and disposition